Sounder exports through changing production - Robbins, Peter (Technical Centre for Agricultural and Rural Cooperation, 2000)
By the start of the millennium, most ACP and other developing countries had liberalised their economies, following the advice of multilateral development agencies. They have undergone structural adjustment programmes and, in becoming members of the...